A randomised controlled trial of three very brief interventions for physical activity in primary care. (December 2016) - Pears, Sally; Bijker, Maaike; Morton, Katie; Vasconcelos, Joana; Parker, Richard; Westgate, Kate; Brage, Soren; Wilson, Ed; Prevost, A.; Kinmonth, Ann-Louise; Griffin, Simon; Sutton, Stephen; et al.
Abstract Background Very brief interventions (VBIs) for physical activity are promising, but there is uncertainty about their potential effectiveness and cost. We assessed potential efficacy, feasibility, acceptability, and cost of three VBIs in primary care, in order to select the most promising intervention for evaluation in a subsequent large-scale RCT. Methods Three hundred and ninety four adults aged 40–74 years were randomised to a Motivational (n  = 83), Pedometer (n  = 74), or Combined (n  = 80) intervention, delivered immediately after a preventative health check in primary care, or control (Health Check only;n  = 157). Potential efficacy was measured as the probability of a positive difference between an intervention arm and the control arm in mean physical activity, measured by accelerometry at 4 weeks. Results For the primary outcome the estimated effect sizes (95 % CI) relative to the Control arm for the Motivational, Pedometer and Combined arms were respectively: +20.3 (−45.0, +85.7), +23.5 (−51.3, +98.3), and −3.1 (−69.3, +63.1) counts per minute. There was a73% probability of a positive effect on physical activity for each of the Motivational and Pedometer VBIs relative to control, but only 46 % for the Combined VBI. Only the Pedometer VBI was deliverable within 5 min. All VBIs were acceptable and low cost. Conclusions Based on the four criteria, the Pedometer VBI was selected for evaluation in a large-scale trial. Trial registration Current Controlled TrialsISRCTN02863077 . Retrospectively registered 05/10/2012.